Gestational trophoblastic neoplasia lethality among Brazilian women: A retrospective national cohort study - Freitas, Fernanda; Braga, Antonio; Viggiano, Mauricio; Velarde, Luis Guillermo Coca; Maesta, Izildinha [UNESP]; Uberti, Elza; Madi, Jose Mauro; Yela, Daniela; Fernandes, Karayna; Silveira, Eduardo; Leal, Elaine; Sun, Sue Yazaki; et al. (Elsevier, 2020)
Objective: To investigate GTN lethality among Brazilian women comparing cases of death by GTN with those who survived, thereby identifying factors associated with GTN lethality. Methods: We retrospectively reviewed medical records of women with GTN treated at ten Brazilian GTN Reference Centers, from January 1960 to December 2017. We evaluated factors associated with death from GTN and used Cox proportional hazards regression models to identify independent variables with significant influence on the risk of death. Results: From 2186 patients with GTN included in this study, 2092 (95.7%) survived and 89 (4%) died due to GTN. When analyzing the relative risk (RR), adjusted for WHO/FIGO score, patients with low risk disease had a significantly higher risk of death if they had choriocarcinoma (RR: 12.40), metastatic disease (RR: 12.57), chemoresistance (RR: 3.18) or initial treatment outside the Reference Center (RR: 12.22). In relation to patients with high-risk GTN, these factors were significantly associated with death due to GTN: the time between the end of antecedent pregnancy and the initiation of chemotherapy (RR: 4.10), metastatic disease (RR: 14.66), especially in brain (RR: 8.73) and liver (RR: 5.76); absence of chemotherapy or initial treatment with single agent chemotherapy (RR: 10.58 and RR: 1.81, respectively), chemoresistance (RR: 3.20) and the initial treatment outside the Reference Center (RR: 28.30). Conclusion: The risk of mortality from low and high-risk GTN can be reduced by referral of these patients to a Reference Center or, if not possible, to involve clinicians in a Reference Center with consultation regarding management.
Keywords: Brazil; Chemotherapy; Choriocarcinoma; Gestational trophoblastic neoplasia; Lethality; Mortality